Journalists’ Subjectivities in Reporting the West Papua Conflict: An APpraisal Analysis - astuti, lidiana; Sakhiyya, Zulfa; -, Yuliati (Language Circle: Journal of Language and Literature, 2025)
This study explores the manifestation of journalistic subjectivity in the coverage of the West Papua conflict by analyzing evaluative language used across three prominent online media outlets: The Diplomat, Al Jazeera, and The Jakarta Post. While journalistic objectivity is traditionally upheld as a fundamental ethical principle, particularly in hard news reporting, it frequently stands in tension with the inherently subjective nature of journalistic practice (Steensen, 2017). This study highlights the need to critically examine how subjective dimensions are subtly interwoven into news discourse. Drawing on the Appraisal Framework (Martin & White, 2005), the research investigates how linguistic resources of attitude, engagement, and graduation are deployed to construct evaluative meanings and shape narrative framing. Annotation conducted via the UAM Corpus Tool 6 reveals a recurrent use of judgement markers, indicating a discursive tendency to assess human behavior and social actors in nuanced way. These patterns suggest that journalistic texts often encode subjective stances through seemingly neutral reporting. Twenty-four students were involved to assess the impact of these evaluative strategies using Likert-scale survey. Findings indicate that subjective language choices significantly shape reader perceptions, thereby underscoring the ideological function of journalism in conflict representation. Beyond its implications for media studies, the findings of this research are expected to contribute to English Language Teaching (ELT) by fostering critical media literacy. It encourages learners to recognize and interrogate the evaluative mechanisms through which language constructs meaning, promoting deeper awareness of how texts position readers.